ginny1029

06-01-2009, 11:37 PM

y= -2 plus/minus the sq rt of 2^2 - 4(1)(-2)

all over

2(1)

y = -2 plus/minus the sq rt of 4 - (-8)

all over

2

y = -2 plus/minus sq rt of 12

all over

2

y = -2 plus/minus sq rt of 4 times 3

all over

2

y= -2 plus/minus 2 sq rt of 3

all over

2

now what do i do i cant cancel the -2 and the 2 out so ????

all over

2(1)

y = -2 plus/minus the sq rt of 4 - (-8)

all over

2

y = -2 plus/minus sq rt of 12

all over

2

y = -2 plus/minus sq rt of 4 times 3

all over

2

y= -2 plus/minus 2 sq rt of 3

all over

2

now what do i do i cant cancel the -2 and the 2 out so ????